"Prospekty (w językach obcych). 1881-1899" - Theodor, Bertling; A., Brockhaus F.; Friedr., Bruckmann; G., Cotta J.; Franz, Duncker; Alphons, Dürr; P., Friesenhahn; [?], Gerlach; G., Grote; Otto, Harrassowitz; [?], Heerdegen; F., Hoblik; et al. (1879)
Bormann's Edwin Selbstverlag, Lipsk 1894, nr 77. - Brockhaus F. A., Lipsk 1883-1895, (5), nr 31-32, 43, 81-82. - Bruckmann's Friedr. Verlag, Monachium 1881, nr 16. - Calvary S. & Co., Berlin 1882, nr 22. - Cohn Albert, Berlin 1891, nr 65. - Cotta'sche J. G. Buchhandlung, Stuttgart 1882-1898, (2), nr 28, 93. - Duncker Franz, Lipsk 1882, nr 20. - Dürr Alphons, Lipsk 1889, nr 57. - Gerlach & Schenk, Wiedeń 1898, nr 91. - Griggs W., Londyn 1884, nr 44. -
1000,00
Keywords: Berlin; księgarnia - Cohn Albert; księgarnia - Calvary S. & Co; księgarnia - Langenscheidt; księgarnia - Asher A. & Co; Allgemeine Verlags-Gesellschaft; księgarnia - Grote G; Königliche Hof-Steindruckerei; Einsiedeln; księgarnia - Benziger & Co; Lipsk; księgarnia - Renger; księgarnia - Schmidt & Günther; księgarnia - Schmidt Caesar; księgarnia - Taubner B. G; Londyn; wydawnictwo - Low Sampson & Co; księgarnia - Watt Alexander P; Mediolan; wydawnictwo - Hoepli Ulrich; Monachium; księgarnia - Hirth G; księgarnia - Rosenthal Ludwig; Verlagsanstalt für Kunst und Wissenschaft; wydawnictwo - Bruckmann Friedr; Nancy; księgarnia - Berger-Levrault & Cie; Norymberga; księgarnia - Heerdegen-Baerbeck; Pardubice; wydawnictwo - Hoblik F; Paryż; księgarnia - Palme Victor; Poznań; księgarnia - Jolowicz Józef; Rostock; wydawnictwo - Werther Wilhelm; Rzym; Stuttgart; księgarnia - Scheible J; wydawnictwo - Neff Paul; księgarnia - Cotta J. G; księgarnia - Kohlkammer W; Wiedeń; księgarnia - Waldheim R. von; wydawnictwo - Gerlach & Schenk; Wiesbaden; księgarnia - Niedner Julius; Wrocław; Museum schlesischer Altertümer; Verein für das Museum Schlesischer Altertümer; Zurych; Augsburg; Literarische Institut von Dr. M. Huttler; księgarnia - Puttkammer & Mühlbrecht; księgarnia - Parey Paul; księgarnia - Wagner R; księgarnia - Wiegand & Grieben; Nicolaische Verlags-Buchhandlung (R. Stricker); księgarnia - Stargardt J. A; księgarnia - Meidinger Herm. J; czasopismo - "Berliner Münz-Blätter"; Brandenburg; księgarnia - Lunitz P; Bruksela; księgarnia - Wytsman P; Darmstadt; księgarnia - Bergstraesser Arnold; Drezno; wydawnictwo - Hoffmann Wilhelm; Düsseldorf; księgarnia - Schwann L; Frankfurt n. M; księgarnia - Rommel Wilhelm; Fryburg Szwajcarski; Librairie de l'Universite (P. Friesenhahn); Gdańsk; księgarnia - Bertling Theodor; Görlitz; wydawnictwo, drukarnia - Starke C. A; Graz; "Styria" Verlagsbuchhandlung; księgarnia - Scholtze Karl; księgarnia - Twietmeyer A; wydawnictwo - Bach J. G; księgarnia - Baumgärtner; księgarnia - Keil Ernst; księgarnia - Harrassowitz Otto; księgarnia - Dürr Alphons; księgarnia - Duncker Franz; wydawnictwo - Bormann Edwin; księgarnia - Brockhaus F. A; Cenniki księgarskie; Katalogi księgarskie; Księgarnie; Ogłoszenia księgarskie; Prospekty